MENINGKATKAN KEMAMPUAN MENYISIR RAMBUT MELALUI TEKNIK MODELING - Desi Yanova (Universitas Negeri Padang, 2012)
The research aimed to efectivitas modelling technic to icrease be able hair comb at the child embisil (X) class III D. at SDLBN Talawi. This research using approach single subject research (SSR) with desain A-B research subject are the child embisil (X). Measure target behavior is are percen (%), the child be able do the hair comb. Intervense with modellings technic gather data to do procedure note with direct ovservation. Make on the format assesment that prepare. That data make on graffic data. Yield research that be able the child hair comb can increase after to give modelling technic. This proven at fase baseline (A) the child be able that only until 53%. After to give intervence (B) a bout technic modelling the child be able to already 90%. From at data can conclusion at modelling technic effective for to increase able hair comb. With purpose to the teacher and the next writer to use modelling that variace on the increase to be able the child embisil.